A symbolic interactionist model of interpreter-facilitated communication—Key communication issues in face-to-face interpreting - Yuan, Xiaohui (Frontiers in Communication, 2022)
Communication has been conceptualised and studied in a wide range of disciplines. However, very few communication theories or models have explicitly incorporated interpreting as an indispensable process to achieve communicative goals in intercultural and interlinguistic settings where communicative parties do not share a common language. By the same token, despite a strong emphasis of interpreting as “a communicative pas de trois” (Wadensjö 1998:12), there is much remaining to be explored in how existing communication theories and models could be drawn on and adapted to shed light on the key communication issues in interpreting studies. In view of such a distinct gap attributed to “a glaring lack of attention from both communication and interpreting scholars”, as highlighted in this special issue, the author develops a symbolic interactionist model of interpreter-facilitated communication with a focus on exploring how an interpreter’s identification with self-meanings and role management, which is key to their intrapersonal covert rehearsal process, impact on their interpreting decisions and behaviours. Through one-to-one interviews with three professional interpreters from the National Register of Public Service Interpreters, it is found that the interpreters’ identification with particular self-meanings at the intrapersonal level, which gives rise to identity integration, identity accumulation and disidentification strategies, has impacted on how they managed various challenges at the interpersonal level, such as the impossibility of the neutrality expectation, dealing with inappropriate non-interpreting demands from communicative parties, and resolving identity conflicts linked to communicative contexts.